Serum ACE2 and Anti-MMR Antibody Profiles in Pediatric Patients with and without SARS-CoV-2 Infection - Labbani-Motlagh, Zohre; Nozarian, Zohreh; Haghi Ashtiani, Mohammad Taghi; Movahedinia, Sajjadeh; Vasei, Mohammad; Hosseini Rouzbahani, Negin (Iranian journal of immunology, 2025)
Coronavirus Disease 2019 (COVID-19) typically manifests with milder symptoms and lower mortality rates in children when compared to adults. To investigate potential mechanisms underlying this age-related protection, we examined whether serum levels of angiotensin-converting enzyme 2 (ACE2) and IgG antibody titers against Measles, Mumps, and Rubella (MMR) vaccines are associated with susceptibility to SARS-CoV-2 infection in the pediatric population. In this case-control study, conducted before the introduction of mass COVID-19 vaccination, we enrolled children aged 1-15 years. The cases were hospitalized children with confirmed COVID-19, while the control group consisted of outpatients with non-infectious, non-immunodeficient conditions and no documented history of COVID-19. The COVID-19 status was confirmed using RT-PCR. Serum levels of ACE2 and anti-MMR IgG antibodies were assessed using ELISA. Eighty-three patients including 39 cases with COVID-19 infection and 44 controls were enrolled in this study. The median serum ACE2 levels were 3.6 in COVID-19 cases and 3.8 ng/mL in control cases (P=0.440). Similarly, antibody levels against Mumps (P=0.788), Measles (P=0.281), and Rubella (P=0.083) did not differ significantly between the groups, although Rubella seropositivity was more frequent in COVID-19 cases than in controls (P=0.039). Our findings did not support a significant association between serum ACE2 levels or MMR antibody titers and protection against COVID-19 in children. The higher prevalence of Rubella seropositivity among infected cases may suggest possible cross-reactivity, but causal relationships could not be established in this study.